The Effect Of The Dash Diet Using The Peer Group Method On Eating Patterns Among Patients With Diabetes Mellitus - Nafolion Nur Rahmat; ⁠Nur Hamim; ⁠⁠Kurniawan ⁠⁠Erman Wicaksono (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Diabetes mellitus (DM) is a chronic disease with a high prevalence in Indonesia, including. One of the main factors influencing the incidence of diabetes is an unhealthy diet. The DASH (Dietary Approaches to Stop Hypertension) diet is a dietary method that has been proven to help control blood pressure and blood sugar metabolism, which is relevant for diabetes management. However, the successful implementation of a diet is often hindered by a lack of knowledge and social support. This study proposes a Peer Group approach as an intervention method to support the success of the DASH diet among diabetes mellitus patients in Kalibuntu Village. The objective of this study is to evaluate the effectiveness of the Peer Group method in implementing the DASH diet among diabetes mellitus patients by measuring changes in dietary patterns and patients’ health status. This study employed a pre-experimental design with a cross-sectional approach, involving a sample of 40 participants selected via purposive sampling, which included the distribution of questionnaires before and after the intervention. The research methods included identifying study subjects, developing the DASH diet module, implementing the Peer Group intervention, analyzing the intervention results, and subsequently publishing the findings.